"Feminists really are crazy": The Isu Station incident and the creation of an androcentric, misogynistic community on YouTube. Issue 2 (3rd April 2023) - Oh, David C.
ABSTRACT: Controversy followed news of an altercation in a Seoul bar between a group of women and men; this was later dubbed the "Isu Station incident." Cellphone video complicated the women's account, providing discursive space to air men's grievances and to discipline recent feminist challenges. The YouTube-distributed video and comments advanced an argument of "enlightened sexism" in which users argued for gender equality while demonizing feminism and claiming reverse sexism. Drawing on hegemonic masculine discourses in South Korea, they created an affective, androcentric, and misogynistic space in which they construct themselves as idealized, tolerant victims of feminist excess.